The Effect of Biorhythm Cycle on Physical Ability of Volleyball Girls - Somayeh Bizadi zadeh; Morteza Nikoofar; Reza Delavar (University of Tehran, 2020)
The aim of the present study was to investigate the effect of biorhythm cycle on physical ability of female volleyball players. The statistical population of the present study included of 120 female volleyball athletes in the age range of 17-20 in 1397 in Boshrouieh city. For this purpose, 30 volleyball female athletes among participants are eligible to enter the study were selected by random sampling. Type of research in terms of purpose has been applied.and in terms of method, it's been semi-experimental which is done by field. In addition According to the date of birth of each subject their biorhythm diagram was plotted and they observed their cycles according to the biorhythm chart and the days of decline and in fitness tests including the Madison Ball throw, to evaluate upper body strength, agility test and vertical sagittal jump, to evaluate lower trunk muscle strength. To analyze the data in addition to using descriptive statistics indices, kolmogorov-Smirnov test and dependent t-test were used. The results showed there was a significant difference between the muscular strength of the subjects in the recharge and discharge days based on the biorhythm cycle (p= 0.035). and also, between the lower trunk muscular strength of subjects on recharge and discharge days based on the biorhythm cycle there is a significant difference (p= 0.004). There is a significant difference between agility of volleyball girls in recharge and discharge days based on biorhythm cycle (p= 0.004).